Expansion of the clinical and molecular spectrum of WWOX‐related epileptic encephalopathy. Issue 3 (19th December 2022) - Chong, Shuk Ching; Cao, Ye; Fung, Eva L. W.; Kleppe, Soledad; Gripp, Karen W.; Hertecant, Jozef; El‐Hattab, Ayman W.; Suleiman, Jehan; Clark, Gary; von Allmen, Gretchen; Rodziyevska, Olga; Lewis, Richard A.; et al.
Abstract: WWOX biallelic loss‐of‐function pathogenic single nucleotide variants (SNVs) and copy number variants (CNVs) including exonic deletions and duplications cause WWOX ‐related epileptic encephalopathy (WOREE) syndrome. This disorder is characterized by refractory epilepsy, axial hypotonia, peripheral hypertonia, progressive microcephaly, and premature death. Here we report five patients with WWOX biallelic predicted null variants identified by exome sequencing (ES), genome sequencing (GS), and/or chromosomal microarray analysis (CMA). SNVs and intragenic deletions of one or more exons were commonly reported in WOREE syndrome patients which made the genetic diagnosis challenging and required a combination of different diagnostic technologies. These patients presented with severe, developmental and epileptic encephalopathy (DEE), and other cardinal features consistent with WOREE syndrome. This report expands the clinical phenotype associated with this condition, including failure to thrive in most patients and epilepsy that responded to a ketogenic diet in three patients. Dysmorphic features and abnormal prenatal findings were not commonly observed. Additionally, recurrent pancreatitis and sensorineural hearing loss each were observed in single patients. In summary, these phenotypic features broaden the clinical spectrum of WOREE syndrome.